Adoção de tecnologia na cultura do milho, em Lavras, Minas Gerais - Ferreira, José Getúlio; Machado Filho, Francisco; G Francis, David; Taranto Fortes, Nicolino (Revista Ceres, 2025)
This study was conducted at Lavras, Minas Gerais, with the main objective to identify and analyze the socioeconomic factors related to the adoption of corn production technology. From the 824 farms studied, four randomly assorted groups of 20, were defined based on the size of the farms. These groups were: 1 — less than 20 ha; II — 20 to 49 ha; III — 50 to 99 ha; IV — 100 ha or more. Stratified sampling was used because in addition to the adoption of technology, the objective included the study of the production systems employed by the farmers within the various strata.